Social media as persuasive technology for business in Malaysia - Hassan, Shahizan; Shiratuddin, Norshuhada; Ab Salam, Sobihatun Nur (IGI Global - All Rights Reserved, 2015)
The use of social media for business purposes has been growing exponentially due to its great potential as an effective marketing tool. Nonetheless, studies which assess how effective social media can be as a persuasive technology are limited, especially in the context of developing countries.Therefore, this study attempts to evaluate the perceived impact of social media as a persuasive technology for businesses in Malaysia. To accomplish this, a questionnaire survey was conducted with 1,196 social media users. Geographical clustering sampling was used, together with simple random sampling to select participants for the survey, which was based in five regions in Malaysia.The outcome of the survey shows that social media can have a significant impact on business and that the majority of social media users perceive that social media content can indeed persuade people to purchase products or services offered. Furthermore, it was found that social media content can also significantly influence purchasing decisions.